"Janisławickie" i "wstęgowe" koncepcje rdzeniowania wiórowego. Próba konfrontacji technologicznej - Wąs, Marcin (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
In the article a comparative analysis of technology of blade production in the late Mesolithic Janislavice culture and early Neolithic Linear Pottery culture is presented. In earlier literature attempts were made to indicate genetic connections of int production of both cultures based on similarities of blade cores and blades morphology. The conducted characteristics of micromorphology of these blade core parts, which play an active part in the production process, is illustrated by different ways of half – raw material production. Two methods of preparation of percussion point on cores: Janislavician cores bear traces of abrasion of core processing edge, „linear” cores have abraded but facetted edges. Both ways were connected with different methods of blade production, and as a result blades of different proportions were formed. Differences between cores of both units are also visible in the shape of flaking the surfaces of blade cores. What is especially distinct is the convexity which reflects itself in the thickness and width of the blades. To conclude, morphological similarities between cores of both cultures seem to be apparent. In actual fact, both units used two different conceptions of blade production. An additional prerequisite for such a statement is a clearly different strategy of halfraw material use, coming from the exploitation of blade cores. In other words – the basic types of tools in the Janislavice culture (microliths, side scrapers) and in the Linear Pottery culture (truncated blades, harvesting knives, end scrapers) needed other forms of half-raw material.